The Effect of Intellectual Capital, Company Size, and Leverage on Profitability in Poultry Industry Subsector Companies Listed on the Indonesia Stock Exchange - Dessy Adelin (Jurnal Office, 2021)
This study aims to examine the effect of intellectual capital, firm size, and leverage on profitability in poultry industry sub-sector companies listed on the Indonesia Stock Exchange for the period 2012-2020. The analysis used in this study uses a fixed effect model with panel data regression analysis. The results showed that Intellectual Capital had no significant effect on profitability. Company size has a negative and significant effect on profitability (ROA). Leverage (DER) has a negative and significant effect on changes in Profitability (ROA) of Intellectual Capital (VAIC), Firm Size (FSZ) and Leverage (DER) together have a positive and significant effect on changes in Profitability (ROA) in listed Poultry Companies on the Indonesia Stock Exchange (IDX) during the period 2012-2020. The coefficient of determination shows the result of 81.36%.